The fin-to-limb transition as the re-organization of a Turing pattern - Koh Onimaru (Nature Portfolio, 2016)
Mouse digit patterning is controlled by a Turing network of Bmp, Sox9, and Wnt. Here, Onimaru et al. show that fin patterning in the catshark, Scyliorhinus canicula, is controlled by the same network with a different spatial organization; thus, the Turing network is deeply conserved in limb development.